Professoras de crianças de 0 a 3 anos: dialogando sobre seus percursos formativos e os desafios enfrentados - Bragatto, Ana Cristina (2013)
The thesis presented here aims to identify which are the learning processes on teacher formation and how them take place, for kindergarten teachers that work specifically with children 0 to 3 years old, at different educational institutions. Through the analysis of the responses given to a structured interview, developed by the researcher, besides communicative reporting and discussion groups guided by the principles of Dialogic Learning, some aspects of the pedagogical practice of six volunteer kindergarten teachers from different educational institutions (one local public, one private and one connected to a public university) have been analyzed; the moments offered by educational institutions that provide training in service for these teachers have been identified; and the obstacles/challenges faced by these teachers on their daily work at the different institutions were identified and analyzed. The techniques for information gathering and the procedures to analyze them respected the postulates of the Critical Communicative Methodology (CCM), developed by the Special Center of Theories and Practices of Overcoming Inequalities (CREA), University of Barcelona, and which is present in researches since the 1990s in Europe. In Brazil it is utilized by the Nucleus of Investigation and Social and Educational Action (NIASE) from Federal University of Sao Carlos (UFSCar) since 2002. This methodology aims to provide a dialogue between the researcher s scientific knowledge and the volunteer teachers practical knowledge. The analyses were guided by the interpretation and description of information between researchers and volunteer teachers, considering the selected social and educational theories, the hypothesis, and the objectives of the research. The conclusions and perspectives found support the hypothesis that indicated failures on initial formation of teachers working with 0 to 3 years old children. These failures are overcome after their professional insertion on the educational institution, and we denominated them as learning processes at the institution . The sources of these learning processes are: the teacher initial reception at the institution; the relationships with their peers, with children and with children s families; the infrastructure offered by the institution, the teacher s work support staff at the institutions; the moments of study and training on the institution and others provided by the institution, and finally, the institutional pedagogic proposal. Beyond the knowledge fonts, it was possible to identify positive practices adopted in a specific institution which allowed suggesting changes to provide maximum learning for children, teachers and families.